Peran Market Orientation, Learning Orientation, Strategic Agility, Strategic Planning, dan Customer Relationship, dengan Innovation sebagai Variabel Mediasi - Listia Nurjanah; Ria Bintan Napitupulu (Journal of Management and Bussines (JOMB), 2023)
The research aims at the role of market orientation, learning orientation, strategic agility, strategic planning, and customer relationships, with innovation as a mediating variable. This research method is descriptive quantitative. The data in this study will be tested with several stages of testing, namely descriptive statistical tests, data quality tests, model evaluation tests, varience inflation factor tests, and hypothesis testing. The results showed that a) market orientation towards innovation had a statistical T value of 0.092<1.96 and a P value of 0.927>0.05; b) learning orientation towards innovation has a T statistic value of 4.228> 1.96 and a P value of 0.000 <0.05; c) strategic agility towards innovation has a statistical T value of 1.328<1.96 and a P value of 0.167>0.05; d) strategic planning for innovation has a statistical T value of 1.740<1.96 and a P value of 0.460>0.05; e) customer relationship to innovation has a T statistic value of 8.315> 1.96 and a P value of 0.000 <0.05; f) innovation on firm performance has a T statistic value of 8.315> 1.96 and a P value of 0.000 <0.05; g) market orientation towards firm performance has a statistical T value of 0.090<1.96 and a P value of 0.929>0.05; h) learning orientation towards firm performance has a statistical T value of 3.861> 1.96 and a P value of 0.000 <0.05; i) strategic agility on firm performance has a statistical T value of 1.454<1.96 and a P value of 0.147>0.05; j) strategic planning for firm performance has a statistical T value of 0.784<1.96 and a P value of 0.455>0.05; k) customer relationship to firm performance has a T statistic value of 5.791> 1.96 and a P value of 0.000 <0.05. In conclusion, learning orientation and customer relationship have a significant positive effect on innovation. Meanwhile, market orientation, strategic agility, and strategic planning do not have a significant positive effect on innovation. Innovation has a significant positive effect on firm performance. Learning orientation and customer relationship have a significant positive effect on firm performance. Meanwhile, market orientation, strategic agility, and strategic planning do not have a significant positive effect on firm performance. Keywords: Firm Performance, Innovation, Learning Orientation, Market Orientation Strategic Agility, Strategic Planning Customer Relations